High Prevalence of Macrolide and Fluoroquinolone Resistance–Mediating Mutations in Mycoplasma genitalium–Positive Urine Specimens From Saskatchewan. Issue 9 (September 2021) - Parmar, Nidhi R.; Mushanski, Linda; Wanlin, Tasker; Lepe, Aurora; Lang, Amanda; Minion, Jessica; Dillon, Jo-Anne R.
Abstract : A high prevalence of Mycoplasma genitalium as well as mutations associated with macrolide and fluoroquinolone resistance was noted in urogenital specimens from Saskatchewan. The prevalence of M. genitalium was higher than for Neisseria gonorrhoeae or Chlamydia trachomatis . Supplemental digital content is available in the text. Abstract : Background: Mycoplasma genitalium is an emerging, sexually transmitted infection, which is more prevalent than Chlamydia trachomatis in some regions. An increase in antibiotic resistance, that is, azithromycin and moxifloxacin, recommended for treating M. genitalium infections has been noted. This is the first detailed report on the prevalence of M. genitalium and its antimicrobial resistance in Saskatchewan, Canada. Methods: Aptima urine specimens (n = 1977), collected for the diagnosis of C. trachomatis / Neisseria gonorrhoeae, were tested for M. genitalium using the Aptima M. genitalium assay (MG-TMA). Antimicrobial resistance was ascertained using polymerase chain reaction and DNA sequencing of 23S rRNA (azithromycin) and parC (moxifloxacin) from Aptima M. genitalium assay–positive specimens; mutations predictive of resistance were noted. Results: The prevalence of M. genitalium was 9.6% (189/1977). Predicted resistance to azithromycin (substitutions at positions 2058/2059 in 23S rRNA) was observed in 63.6% (70/110) of the specimens tested, whereas resistance to moxifloxacin (S83I in ParC) was observed in 10.6% (9/85) of the specimens. Mutations in both 23S rRNA and ParC were observed in 2.12% (4/189) of the specimens. Women aged 20 to 24 years had the highest prevalence (18.3%, P < 0.001), and in females, M. genitalium was significantly associated with C. trachomatis or N. gonorrhoeae / C. trachomatis ( P < 0.001) coinfection. The prevalence of M. genitalium (9.6%) in the province of Saskatchewan was higher than that of the other 2 bacterial sexually transmitted infections ( N. gonorrhoeae (3.09%) and C. trachomatis (6.85%). Conclusions: The prevalence of M. genitalium (9.6%) and associated resistance to azithromycin (63.6%) in Saskatchewan high, suggesting that empiric azithromycin therapy may not be adequate for treating M. genitalium infections.